2016
DOI: 10.22499/3.6602.006
|View full text |Cite
|
Sign up to set email alerts
|

Links between East Coast Lows and the spatial and temporal variability of rainfall along the eastern seaboard of Australia

Abstract: East Coast Lows (ECLs) are intense low-pressure systems which occur over the subtropical east coasts of southern and northern hemisphere continents. ECLs are typically associated with gale force winds, large seas, storm surges, heavy rainfall and flooding. While ECL impacts are typically seen as negative the rainfall associated with ECLs is also very important for urban water security within the heavily populated eastern seaboard of Australia (ESA). This study investigates historical ECLs to gain insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The low interannual variability reflects much larger variations in the prevailing types of cyclones in each year, with only weak correlations between the overall frequency of surface vs upper cyclones (r ¼ 0.28) and generally weak correlations between the five subcategories, including between strong and weak surface cyclones (r ¼ 0.05) or between strong and weak upper cyclones (r ¼ 0.26). This has also been identified using other methods of subcategorising ECLs, with seasons that have a high frequency of cyclones typically dominated by cyclones with a similar synoptic signature (Browning and Goodwin 2016;Kiem et al 2016). The interannual variability of deep cyclones is particularly large, between 4 days in 1994 and 30 days in 1990.…”
Section: Trends and Variability Of Cyclonesmentioning
confidence: 73%
See 1 more Smart Citation
“…The low interannual variability reflects much larger variations in the prevailing types of cyclones in each year, with only weak correlations between the overall frequency of surface vs upper cyclones (r ¼ 0.28) and generally weak correlations between the five subcategories, including between strong and weak surface cyclones (r ¼ 0.05) or between strong and weak upper cyclones (r ¼ 0.26). This has also been identified using other methods of subcategorising ECLs, with seasons that have a high frequency of cyclones typically dominated by cyclones with a similar synoptic signature (Browning and Goodwin 2016;Kiem et al 2016). The interannual variability of deep cyclones is particularly large, between 4 days in 1994 and 30 days in 1990.…”
Section: Trends and Variability Of Cyclonesmentioning
confidence: 73%
“…For the purposes of this analysis, we focused on rainfall along the highly populated coast east of the Great Dividing Range, known as the eastern seaboard (ESB). This was defined similarly to previous studies (Timbal 2010;Kiem et al 2016;Pepler et al 2016b) and is indicated with a polygon throughout the paper (e.g. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Work to address this need is underway at BoM (e.g. the MATCHES ECL computer database) and also as part of ESCCI (see for example Kiem et al 2016).…”
Section: A) B)mentioning
confidence: 99%
“…This study will not explicitly look at ECL impacts on water security but we reference ECL dynamics as motivation for this study. Kiem et al (2016) describes these dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…1. Investigate ECL formation, impacts, historical variability and future projections (see Kiem et al 2016). 2.…”
Section: Introductionmentioning
confidence: 99%